CO2 EMISSIONS and MACROECONOMICS INDICATORS in EMERGING MARKET COUNTRIES - Johari, Anastasya Aprilia; Azwardi (Journal of Economic Development, Environment and People, 2025)
The increasing economic growth in emerging market countries has led to rising concerns about environmental sustainability, particularly CO2 emissions. This study aims to analyze the effect of GDP per capita, Foreign Direct Investment (FDI), and Government Expenditure on CO2 emissions in five emerging economies (Indonesia, India, China, Russia, and Brazil) during the 1998–2022 period using panel data analysis techniques. By applying the Chow and Hausman tests, the Fixed Effect Model (FEM) is identified as the best model for this study. The findings indicate that GDP per capita positively and significantly influences CO2 emissions, supporting the Environmental Kuznets Curve (EKC) hypothesis. Conversely, FDI has a negative and significant effect, aligning with the Pollution Halo Hypothesis, as foreign investments introduce environmentally friendly technologies. Similarly, Government Expenditure negatively and significantly influences CO2 emissions, highlighting the role of public spending in promoting sustainable infrastructure and reducing emissions. These findings suggest that sustainable economic growth, increased public spending on green projects, and incentivizing environmentally friendly FDI are essential for balancing economic growth and environmental sustainability in emerging economies.